Effect of Thermal Convection and Mass Transfer on Particle Motion During Sedimentation: A Numerical Study (Advances in Applied Mathematics and Mechanics, 2024)
The sedimentation of a particle cluster with heat and mass transfer is studied with the lattice Boltzmann method. To investigate the effect of thermal convectionand mass transfer on the motion of the particle cluster, four cases are studied, namely,without heat and mass transfer, with heat transfer, with mass transfer and with heatand mass transfer. Compared to mass transfer, the effect of thermal convection is moredominant, which affects the motion of the particle cluster significantly. The particle-particle interaction is enforced by thermal convection, and the oscillation of the average settling velocity of the particle cluster is more intense. Besides, with mass transferbetween the particles and the fluid, the mass of the particles decreases, the motion ofthe particles is more sensitive to the fluid flow, the velocity fluctuation of the particlecluster is more intense, the distribution of the particle cluster is more inhomogeneous.